If it's not what You are looking for type in the equation solver your own equation and let us solve it.
14-3v=11
We move all terms to the left:
14-3v-(11)=0
We add all the numbers together, and all the variables
-3v+3=0
We move all terms containing v to the left, all other terms to the right
-3v=-3
v=-3/-3
v=1
| 56-7x=2x+22 | | x-2.3=10.2 | | 12x2+4x=8 | | -5(5x+9)=-3(9x+5) | | w/2-15=1 | | 3.4x-8.34=5.6 | | 37=v/7+17 | | g/3=7 | | 6x-12=5x+17+x | | 6x+10=2(5x-3) | | n+2.4=3.9 | | 5=v/6-1 | | 6=36*√a/25 | | -2x=3=-19 | | 8x-7-2x=-67 | | 5=q-24.2 | | 1/3/4+z=2/2/3 | | -2b-3+5b=6 | | n5− 1=3 | | 10+(1)/(3)y=1 | | -27=–3p+15–3p | | -18=4q+-10 | | 4.3=v+6 | | -8=4q+-10 | | (4x+12)=(5x-4) | | z+33/9=7 | | k/7+20=26 | | -53=10+-9d | | 4x-2(x-6)=-10 | | 5x2+25=75 | | 5(s+4)=90 | | -4(w+10)=20 |